Improving The Perception of The Names of Objects Through Learning Media in Elementary School - Syarial Syarial (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2021)
The purpose of this study is to find an increase in the learning process and students' perceptions of objects around us to provide understanding when the object is said to be a dangerous tool or not through the suitable media, namely learning videos. This research method used classroom action research (CAR). The subjects in this study were fifth-grade students at the SDN (Public Elementary School) 18 Parit Setia, Jawai sub-district, Sambas district, with 20 students consisting of 8 male students and 12 female students. 35% and 13 students have not graduated with a percentage of 65%, continue to first cycle increasing to 16 students are said to have passed with a percentage of 80% and who have not passed four students with a percentage of 20% in the second cycle, the researchers try to improve the learning process by using the learning video variant and increased to 100% pass which amounted to 20 students. Conclusions that can be submitted and taken are that the learning process using video is very effective for giving perceptions of objects around us, both harmful and not harmful in terms of size, color, and the form of object names.